Analysis of the relationship between fetal magnetic resonance imaging indications and findings with ultrasonographic examination - Akselim, Burak; Karaşin, Süleyman Serkan; Şenkutlu Kuyucu, Beril (The European Research Journal, 2021)
Objectives: We aimed to examine the indications for the use of fetal MRI in obstetrics practice and the relationship between fetal MRI and ultrasonographic findings. Methods: Seventy-three patients were examined with Fetal MRI for various reasons between July 2017 and July 2020, and whose results were available were evaluated retrospectively. Ultrasonographic and MRI findings were recorded. The detected pathologies were divided into groups according to systems. The relationship between the findings was examined. Results: In our study, ultrasonographic findings of fifty-five (75.3%) cases were confirmed by MR findings. MRI detected additional findings in eight (10.9%) cases, most of which were intracranial pathologies. The most detected ultrasonographic findings as an indication for the request were in the intracranial region (54.8%). Conclusions: Fetal MRI indications in perinatal care and follow-up are not clear. Determining these indications is also essential in preventing unnecessary use in obstetric practice and determining the cost-effectiveness.